Impact of physical and skill exercise in development of the carrying the special speed of motor performance and skill performance for football players - Khalil, Nabil (Journal of Physical Education, 2015)
This study was conducted on a sample of the football players within the Zafaraniya team, which numbered (20) as a player and the age of (18-20 years). This study aims to identify the impact of physical and skill exercises in development of the carrying the special speed of the motor and skill performance in football for the research sample. The results of this study, the presence of significant differences between the tribal and a posteriori tests in favor of a posteriori tests to sample differences. One result of this study is also an improvement in the level of carry-speed motor performance and improvement in the level of performance skills of speed performance skills to the skill of dribbling and rolling in sample members of the experimental group as much larger than the control group